2018
DOI: 10.1002/adts.201800054
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Regulation of Spontaneous Water Transport in Graphene‐Based Nanoslits

Abstract: While nanometer-scale capillaries have long been theoretically and experimentally studied, their transport mechanisms have not yet been fully understood. Here, the flow control mechanism is theoretically clarified by molecular dynamics (MD) simulations of graphene-based nanoscale capillaries. The imbibition rate complies with a modified Lucas-Washburn equation. It changes non-monotonically with the slit width due to a compromise in competition of density and slip length. Secondly, the relative scale of imbibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…[152] Therefore, the interaction between water molecules around hydrated ions and graphene membranes in the nanochannels could make the ions almost frictionless through the graphene layers. MD simulations have found that water can spontaneously and rapidly pass through graphene nanochannels.…”
Section: Ion Distribution and Diffusion In Nanochannelsmentioning
confidence: 99%
See 1 more Smart Citation
“…[152] Therefore, the interaction between water molecules around hydrated ions and graphene membranes in the nanochannels could make the ions almost frictionless through the graphene layers. MD simulations have found that water can spontaneously and rapidly pass through graphene nanochannels.…”
Section: Ion Distribution and Diffusion In Nanochannelsmentioning
confidence: 99%
“…MD simulations have found that water can spontaneously and rapidly pass through graphene nanochannels. [152] Therefore, the interaction between water molecules around hydrated ions and graphene membranes in the nanochannels could make the ions almost frictionless through the graphene layers. Early studies have found that the diffusion coefficients of ions and water confined in neutral channels are larger than those in bulk solution because of the incomplete solvation of ions and the low average water molecule density.…”
Section: Ion Distribution and Diffusion In Nanochannelsmentioning
confidence: 99%